Manajemen Humas: Membangun Peran Masyarakat dalam Lembaga Pendidikan - Lauchia, Rara; Maulana, Hafidz; Setiyadi, Bradley (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to find out how big the role of stakeholders, in this case educational institutions, is in building public relations, especially at Madrasah Aliyah Negeri 2 Lubuklinggau, and then to find out what participation is given by the community for the advancement of education. The method used in this research is a qualitative case study. The results of this research show that Madrasah Aliyah Negeri 2 Lubuklinggau implements good public relations management, able to make the community participate in advancing education at the institution.